AMQM System for Measuring the Quality of Postal Services - Spajić, Drago; Šapina, Krešimir (Promet - Traffic&Transportation)
The work presents the AMQM (Automatic Mail QualityMeasurement) system for measuring the quality of postal services.The system has been developed at the request of UPUtheworld postal union. AMQM represents an advanced managerialtools whose main task is to obtain objective data on thequality of providing postal services. Based on the obtained datafrom the AMQM system, the activities may be planned whichare necessary for quality improvement of postal services.